A new species of Parathyone (Holothuroidea: Dendrochirotida: Cucumariidae) from northeastern Brazil, with a key to species - Martins, Luciana; Tavares, Marcos (Zootaxa, 2021)
A new species of Dendrochirotida sea cucumber, Parathyone itapuaensis, is described and illustrated herein based on specimens collected from rocky intertidal regions of the northeastern coast of Brazil. The new species is characterized by a suite of morphological characters revealed by light stereomicroscope, SEM and microCT studies of the calcareous ring, dermal ossicles, Polian vesicles and madreporite. Parathyone itapuaensis sp. nov. is characterized by having 10 tentacles, two Polian vesicles and single madreporite; length of anterior process (radial plate) larger than length of the base of the radial plate; body wall with buttons with triangular knobs and knobbed multiperforated plates in the anal region; and tentacles with arched rods, knobbed in the margins and shallow cups knobbed in the outer and inner surfaces. A key to the recognition of Parathyone species is given.